2014
DOI: 10.1186/s40201-014-0148-9
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Phase adsorption kinetics and equilibrium of toluene by novel modified-diatomite

Abstract: The adsorption equilibria of toluene from aqueous solutions on natural and modified diatomite were examined at different operation parameters such as pH, contact time, initial toluene concentration was evaluated and optimum experimental conditions were identified. The surface area and morphology of the nanoparticles were characterized by SEM, BET, XRD, FTIR and EDX analysis. It was found that in order to obtain the highest possible removal of toluene, the experiments can be carried out at pH 6, temperature 25°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The Freundlich isotherm model equation is expressed as: where Q m indicates saturated adsorption capacity (mg/g); K L represents adsorption energy correlation constant; K F is the Freundlich adsorption capacity coefficient; and 1/n is the correlation coefficient of resin capacity [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Freundlich isotherm model equation is expressed as: where Q m indicates saturated adsorption capacity (mg/g); K L represents adsorption energy correlation constant; K F is the Freundlich adsorption capacity coefficient; and 1/n is the correlation coefficient of resin capacity [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The other two vibrations at around 1023 cm −1 and 465 cm −1 were related to the asymmetric stretching vibration mode of siloxane (Si-O-Si) [27]. The peak at 786 cm −1 was attributed to Al-O-Si stretching vibration according to the clay minerals in diatomite [28].…”
Section: Ftir Studiesmentioning
confidence: 97%
“…Although adsorption in liquid phase has been widely used in the processes mentioned at the beginning of the introduction, it has been studied mainly for the aqueous phase [ 17 , 18 , 19 , 20 ], but little has been investigated about liquid phase adsorption for hydrocarbons when the solvent is another nonpolar organic substance [ 18 ], due to the research found is related to the usage of water as a solvent [ 17 , 18 , 19 , 20 ]; therefore, the study of systems of this type is interesting, since low-molecular-weight hydrocarbons are within the Volatile Organic Compounds (VOCs) which, due to their characteristics, can be in the environment in the gas and liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…So, the interesting aspect of this work is that nonpolar solutions are evaluated; this is a field that is not so commonly studied because it is more usual to find research that investigates aqueous systems [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%